(3GdeLeds - (3GHf aGQS , CHh GdMSjf CMeO Hf aGQS Hf RcQjGA GdbRhjfj GdQGRj,J (B395 (3g` s ((3CHhHcQ eMeO Hf ehSi GdNhHi s)
(3ChdgG (B:s
(3jHOC GdehLhO efg HcJGH GdhGh HGH GdhGh heG HYOgG ai GdeVGYa hGdeWGHb s
(3BNQgG (B:s
(3jfJgi HcJGH GdjGA HGH GdjGA heG HYOgG eeG gh Ydi MQajf gPG BNQ eLed GddZI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B193 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B40s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1604s
Keywords: (3GddZIs